Profiling elite stand up paddle boarders - Schram, B.; Hing, W.; Climstein, M.; Walsh, J. (Journal of Fitness Research, 2014)
Introduction: Stand up paddle boarding (SUP) is a rapidly growing sport and recreational activity where anecdotal evidence exists for its proposed fitness, injury rehabilitation & core strength benefits. A review of the literature failed to identify a single article which examined the potential physiological adaptations associated with SUP.